Fabrication of human genomic DNA encapsulated supermacroporous alginate beads - Pasandideh, Ramona; Gazi, Mustafa; Terali, Kerem; Oladipo, Akeem Adeyemi (Taylor & Francis Ltd, 2021)
Here, human genomic DNA (hDNA) was encapsulated into supermacroporous alginate beads (SMPA) fabricated via microinjection and freeze-thawing cryogelation protocol. The scanning electron microscopy of the SMPA beads demonstrated smooth and centred burgled morphologies, while the encapsulated hDNA showed brilliant green fluorescence when visualised by fluorescence microscopy. The encapsulation efficiency of 89.1 - 96.7% was achieved when the concentration of hDNA and alginate varied within 0.05 - 0.075% and 0.5 - 0.75 wt%, respectively in the presence of 0.1 M CaCl2 crosslinking agent. 80% hDNA was released over an extended period of 80 h when SMPA was immersed in a 0.5 M Na2HPO solution diluted with 10 mM Tris buffer (pH 7). Results and trends here demonstrated that SMPA beads have great potential to be used as a biocompatible vehicle for transporting biomacromolecules.
Keywords: Controlled release systems; human genomic DNA; alginate polymeric cryobeads; supermacroporous; gene therapy